FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN PERSALINAN PREMATUR (Studi di RSUD Lamaddukkelleng Kabupaten Wajo) - Reskiawati Azis; Muliyana (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2021)
Introduction : This research aims to find out the factors related to the incidence of premature childbirth at Lamaddukkelleng Regional General Hospital wajo regency. Method: Research uses analytical surveys with the Cross sectional Study approach. The population is all maternity mothers in the intranatal room of Lamaddukkelleng Regional General Hospital wajo regency numbering 168 people. Sampling using purposive sampling techniques with solvin formula as many as 63 respondents. Data collection through primary data (chek list sheet) and secondary data. The data was processed using Statistical Program for Social Science (SPSS) version 16.0 and analyzed univariate and bivariate with chi square statistical tests (X²) and presented in the form of frequency distribution and analysis tables. Results: Bivariate analysis found there was a relationship between maternal age and premature childbirth (?value=0.001<0.05), there was a relationship of parity with premature childbirth (?value=0.002<0.05), and there was a relationship of pregnancy distance with premature childbirth (?value=0.001<0.05). Conclusion: variables have the potential to undergo premature childbirth, so the need for counseling in the community on the importance of maternal age, parity, and distance of pregnancy to the risk of premature childbirth